Effect Of carbon fiber loading in gaphite-polypropylene composite properties as bipolar plate for polymer electrolyte membrane fuel cell - Selamat, Mohd Zulkefli; Jamil, Noor Ashikin; Hasan, Rafidah; Dhar Malingam, Sivakumar (Malaysian Society of Analytical Sciences, 2021)
The performance of Polymer Electrolyte Membrane Fuel Cells (PEMFC) is dependent on the properties of bipolar plates (BP). In this research, the BP had been developed using hybrid fillers; graphite (G) as the main filler and carbon fiber (CF) as the second filler while polypropylene (PP) as a binder in G/CF/PP composite. All materials were in powdered form and the composition of this composite was fixed at 80% (fillers) and 20% (PP). The contents of CF was varied from 5% up to 20% of the total weight of fillers (80%). Ball mill was used to mix the fillers and binder together before being pressed by compression molding (hot press) in a rectangular shape (140 mm x 60 mm) mould. The electrical and mechanical properties of the developed composite were measured to investigate its suitability of BP to be used as PEMFC. The result showed that the electrical and mechanical properties decreased as the loading of CF was increased. The composite with 5% of CF loading showed the highest value of electrical conductivity (262.75 S/cm) and flexural strength (40.2 Mpa). Images of the fractured surface for G/CF/PP composites for various CF contents was determined by Scanning Electron Microscope (SEM). This finding shows that the properties G/CF/PP composite is suitable for BP of PEMFC in the future.